Skills and Training Requirements for the Future Transportation Sector of Europe - E. Bekiaris; M. Loukea (Наука и техника)
More than 10 million people are directly employed by the transport industry in Europe, accounting for 4.5 % of total employment and representing 4.6 % of Gross Domestic Product (GDP). This fact, combined with the rapid developments and changes of the sector, makes imperative the need to create, attract and retain appropriate staff. As the overall trend is to increase automation, the sector will depend more and more on specialised equipment and products. Future jobs will therefore require new and advanced skills in engineering as well as in back office operations, but at the same time, the growing interdisciplinary elements of transport activities will also require transport professionals with developed skills in safety, security, logistics, IT, behavioural sciences, marketing and economics. The European Research project SKILLFUL has developed a structured foresight into the vocational and academic qualifications in the Transportation sector of the future and has proposed training schemes and their supportive business models that could ideally be adopted European-wide, to enhance employability and sustainable industrial development in the transportation sector in Europe. The identification of future requirements constituted the basis of the project. The impact of new technologies and game changers, as well as emphasis on intermodality and interdisciplinarity on employability and future worker skills, have led to the development of relevant scenarios on future jobs knowledge and skills requirements, regarding the road transport in Europe. This has led to the identification and design of proper and specific curricula for training (with emphasis on middle-skilled professionals and lifelong learning), while also to the introduction of six novel concepts of business actors, expected to facilitate the training process and enhance the transport-education chain. The project goes a step beyond by addressing also critical issues towards a PanEuropean master curriculum on transport.